The Influence of International Law on State Sovereignty and Human Rights - Dr Anwar ul Mustafa Shah; Dr. Farhana Kousar; Abdul Sattar Khokhar (Journal of Religion and Society, 2025)
This article examines the evolving relationship between international law, state sovereignty, and the promotion of human rights in the contemporary global order. Historically, the principle of sovereignty, rooted in the 1648 Treaty of Westphalia, has granted states the supreme authority within their territories, free from external interference. However, the post-World War II era marked a paradigm shift, with the rise of international legal frameworks such as the United Nations Charter and the Universal Declaration of Human Rights, establishing norms that transcend national boundaries. These developments introduced new legal and moral obligations that often challenge the traditional concept of absolute sovereignty. The paper explores the historical evolution of sovereignty, the legal mechanisms that promote human rights, and the theoretical tensions between state autonomy and international norms. It analyzes key legal instruments, including the ICCPR, ICESCR, and ECHR, alongside institutions like the ICC, ICJ, and UNHRC. The study also discusses state practice in human rights compliance, highlighting issues of selective enforcement and the challenges faced by developing nations in integrating international norms into domestic legal systems. Regional perspectives, such as those of the African Union, European Union, and ASEAN, are evaluated for their unique approaches to balancing sovereignty and human rights. Contemporary challenges including populism, digital sovereignty, and climate-induced human rights crises underscore the urgency of rethinking how sovereignty and international law can be harmonized. The article concludes with policy recommendations aimed at enhancing legal cooperation, strengthening institutional mechanisms, and fostering global consensus on the universality of human rights. Overall, the research provides a comprehensive overview of how international law influences, constrains, and complements state sovereignty in the pursuit of a more just and accountable international system. Keywords: State Sovereignty, International Law, Human Rights, R2P, ICJ, UNHRC, Digital Sovereignty, Customary Law, Global Governance, Enforcement Mechanisms